Specialist Library versus Generalist Library: Document Selection - Ranganathan, S. R.; Gopinath, M. A. (Journal of Information and Knowledge, 1968)
This is a report of three classes in DRTC, extending over five hours, conducted by Dr Ranganathan, on 21, 22, and 23 March 1967. Singles out the techniques distinctive to a Specialist Library from that of a Generalist Library, on the basis of the Five Laws of Library Science. They are: Individual approach to ascertain specialist interest as against statistical approach in a Generalist Library (Law 1); Informal talks with each specialist as against mass survey (Law 2); Restricting the acquisition of periodicals to those having at least 40 per cent of their articles relevant to the subject-interest of a Specialist Library (Law 3); Coordination in acquisition of periodicals and cooperation among libraries (Law 2 and 3); Acquisition of indexing periodicals, abstracting periodicals, trend reports, short communication periodicals, and preview type periodicals (Law 4); and Drastic weeding out of obsolete documents in a Specialist Library (Law 5). The usual annotations highlighting the educational principles followed in the class are added.